EFFICACY OF CORMOBID OCTEOARTHROSIS WITH ARTERIAL HYPERTENSION CONTROL CONSIDERING THE TYPES OF ORTHOSTATIC REACTIONS AND CARCADIAN PROFILES OF ARTERIAL PRESSURE - Soldatenko, I. V.; Lysenko, N. V.; Tomina, O. E.; Kulyk, V. L. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Clinical peculiarities, heart rate variability and effectiveness of comorbid osteoarthrosis with arterial hy-pertension control considering the types of orthostatic reactions and circadian profiles of blood pressure were established. In patients with comorbid osteoarthrosis with arterial hypertension all three types of systolic and diastolic blood pressure orthostatic reactions with the prevalence of hypertensive were observed, and all of four types of diurnal profiles – with a prevalence of non-dipper on systolic blood pressure and dipper for diastolic. The detrimental types of arterial pressure orthostatic responses were observed in 12 % of systolic and in 15 % of diastolic type in patients with comorbid OA with AH then with isolated one. Migration regula-rities of blood pressure orthostatic reactions in patients with comorbid osteoarthrosis with arterial hypertensi-on on the stages of therapy were revealed and it was determined that migration of systolic blood pressure was higher into the hypertensive type, diastolic – into hypotensive. It was determined that comorbid with arterial hypertension osteoarthrosis had no effect on baseline indexes of heart rate variability, but affected the reac-tions on orthostasis. In the management of patients it should be taken into account that in hypotensive and isotensive of orthostatic reactions, dipper and night-peaker circadian profiles of systolic blood pressure and night-peaker profiles of diastolic blood pressure require more intensive antihypertensive therapy. In studied clinical signs and heart rate variability indices statistically significant criteria of arterial hypertension comor-bid with osteoarthrosis efficacy control were patients age and sympatho-vagal balance ratio.